Internal employer brand, employee engagement and perceived organizational support:A review of literature - Wang, Junjie; Wang , Jingwen (Transactions on Economics, Business and Management Research, 2024)
The satisfaction of existing employees and the retention of talents are the basic elements of organizational success. In this context, this study intends to build a research model of "internal employer branding - perceived organizational support - employee engagement", aiming to explore whether the process and method of employer brand building within an enterprise can improve the engagement of existing employees. Employer branding was initiated by Ambler and Barrow (1996) with an aim to attract and retain the best talent through various activities, and the contemporary research has proven that if branding of the organization is done in an effective manner then it retains the best talent; further, it enhances job engagement and motivation. The present chapter elaborates the concept of employer branding, benefits, and importance of employer branding. Recent surveys and trends of employer branding have also been discussed, Perceived organizational support may be another important antecedent variable for employer branding.